The estimation of residual stresses by the brittle thin film's initial cracks on a ductile substrate subjected to tensile stresses. (October 2021) - Wang, Qi; Li, Lin-An; Li, Chuanwei; Li, Jun; Wang, Zhiyong; Wang, Shibin; Zeng, Yantao
Highlights: A model concerning crack morphology and residual stress in films is constructed. A method of residual stress estimation is proposed. Experiments verify the correctness of the method. Abstract: Thin metal films in the nanometer range are extensively used for electronic and optoelectronic devices. However, the residual stress has a profound impact on the durability of the devices during their lifetime. This paper developed a two-dimensional (2D) elastic model to study the residual stress and opening-mode fractures (OMFs) in a film/substrate assembly. The fracture strength expressed by crack length is derived by the strength criterion. This paper also studies fragmentation of 100–400 nm thin Cr films on 125 μm polyimide substrates. The residual stress in the coating process is estimated based on the onset strains of fragmentation. For films with thicknesses of 100 nm, 200 nm, and 400 nm, the estimated residual stresses are −1.204 GPa, −0.889 GPa, and −0.305 GPa respectively. This method shows more convenient than some traditional methods (including the use of X-ray diffraction technique or other methods of determining curvature). The tensile fragmentation tests would provide data to verify the accuracy of the estimation during crack accumulation; a good agreement is found between the experimental results and those predicted using the estimated residual stresses.